Elecciones presidenciales en Argentina 2003 - Rodríguez Kauth, Ángel; Universidad Nacional de San Luis (Instituto de Estudios Políticos. Universidad Central de Venezuela, 2013)
A partir de una apretada síntesis de lo ocurrido en Argentina desde la derrota de la Alianza gobernante –en diciembre de 2001– se hace la lectura del resultado de las elecciones presidenciales de 2003. Sobre ellas se hace un análisis político no sólo del resultado de la primera vuelta, sino también de las vicisitudes que se sucedieron previo al ballottage –que no pudo realizarse por la renuncia de Menem a participaren él– y las posibilidades de gobernabilidad de las nuevas autoridades.Presidential elections in Argentina 2003AbstractBeginning with a concise overlook of the events in Argentina following the defeat of the governing Alliance –in December 2001– this extract focuses on the results of the 2003 presidentialelections. In this connection, a political analysis is performed not only of the first-roundresults, but also of the events prior to the ballottage –which could not be carried out as a result of Menem’s refusal to take part there in– and the possibilities of governance for new authorities.